Porphyromonas gingivalis fimbriae induce a 68-kilodalton phosphorylated protein in macrophages. - Murakami, Y (1994)
The present study was performed to examine whether Porphyromonas gingivalis fimbriae induce specifically a protein kinase-mediated phosphorylated protein that is involved in the mechanism of signal transduction. The fimbriae induced a 68-kDa phosphorylated protein (pp68) in a dose-dependent manner in mouse peritoneal macrophages. A marked appearance of pp68 was observed 20 min after the initiation of fimbrial treatment. The fimbria-induced pp68 was inhibited dramatically by staurosporine, a potent inhibitor of protein kinase C. pp68 induction was also inhibited by H-7, a potent inhibitor of several types of protein kinase. However, the induction was not inhibited by HA-1004 and H-8, relatively high-affinity inhibitors of protein kinase A. Phorbol myristate acetate and 1-oleoyl-2-acetyl-sn-glycerol, activators of protein kinase C, were able to induce pp68 in mouse peritoneal macrophages. This protein was localized in the cytosolic fraction of fimbria-treated macrophages. pp68 also was induced in fimbria-treated human monocyte-like cells. Finally, we observed that gene expression of the fimbria-induced neutrophil chemoattractant KC was inhibited markedly by staurosporine.